Global Lysine Acetylome Analysis of Desiccated Somatic Embryos of Picea asperata - Xia, Yan; Jing, Danlong; Kong, Lisheng; Zhang, Jianwei; OuYang, Fangqun; Zhang, Hanguo; Wang, Junhui; Zhang, Shougong (Frontiers in Plant Science, 2016)
Partial desiccation treatment (PDT) promotes the germination capacity of conifer somatic embryos. Lysine acetylation (LysAc) is a dynamic and reversible post-translational modification that plays a key role in many biological processes including metabolic pathways and stress response. To investigate the functional impact of LysAc in the response of Picea asperata somatic embryos to PDT, we performed a global lysine acetylome analysis. Here, combining antibody-based affinity enrichment and high-resolution mass spectrometry, we identified and validated 1079 acetylation sites in 556 acetylated proteins from P. asperata somatic embryos during PDT. These data represent a novel large-scale dataset of lysine-acetylated proteins from the conifer family. Intensive bioinformatics analysis of the Gene Ontology of molecular functions demonstrated that lysine-acetylated proteins were mainly associated with binding, catalytic activities, and structural molecular activities. Functional characterization of the acetylated proteins revealed that in the desiccated somatic embryos, LysAc is mainly involved in the response to stress and central metabolism. Accordingly, the majority of these interacting proteins were also highly enriched in ribosome, proteasome, spliceosome, and carbon metabolism clusters. This work provides the most comprehensive profile of LysAc for a coniferous species obtained to date and facilitates the systematic study of the physiological role of LysAc in desiccated somatic embryos of P. asperata.